2015
DOI: 10.1016/j.ijms.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of chromium-cobalt binary cluster formation by pulsed laser evaporation

Abstract: Intermetallic clusters are observed in the Co-Cr system. We report on the use of time of flight mass spectroscopy to investigate the cluster spectrum resulting from Nd-YAG ablation of a CoCr target. Cr + clusters dominated the spectrum, with Co + clusters as the second most intense peak, and we found a clearly resolved Cr-Co binary cluster that could be suitable for co-doping during the growth of laser crystals. Significant contributions from elemental dimers as well as some oxide clusters were also observed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Nanoparticle formation via laser ablation of target materials has been reported elsewhere [29]. It has also been reported that Co−Cr binary clusters along with Cr + and Co + clusters are formed via laser ablation of a Co−Cr target [30]. These clusters may be involved in the formation of the CoCr 2 O 4 nanoparticles in the LAB process.…”
Section: Discussionmentioning
confidence: 79%
“…Nanoparticle formation via laser ablation of target materials has been reported elsewhere [29]. It has also been reported that Co−Cr binary clusters along with Cr + and Co + clusters are formed via laser ablation of a Co−Cr target [30]. These clusters may be involved in the formation of the CoCr 2 O 4 nanoparticles in the LAB process.…”
Section: Discussionmentioning
confidence: 79%